IMPLEMENTATION OF TABALONG REGENT REGULATION NUMBER 60 OF 2019 CONCERNING LAND AND BUILDING RIGHTS ACQUISITION FEES (BPHTB) AT THE REGIONAL REVENUE AGENCY OF TABALONG REGENCY - Rasyidah; Jauhar Arifin (JAPB, 2023)
It is important to implement Tabalong Regent Regulation Number 60 of 2019 concerning land and building rights acquisition fees (BPHTB) at the Tabalong Regency Regional Revenue Agency because problems were found related to the slow service rendered, thus hampering the payment of Land and Building Rights Acquisition Fees (BPHTB) carried out by the people of Tabalong Regency. In this study, the data analysis used was analytical descriptive analysis, namely revealing a problem and a situation as they are. The process of data analysis begins with examining all the data obtained both through observations and questionnaires. The population in this study amounted to 61 people. The samples taken were from 61 people. The analysis technique in this study is described using percentage analysis. Based on the results of the recapitulation of respondents' answers related to indicators of size and policy goals, resources, characteristics of implementing agents, attitudes or tendencies (dispositions) of implementers, communication between organizations and implementing activities, and the social, economic, and political environment, it can be said to have been going well. This is supported by the answers of respondents totaling 61 people, of whom 61 found the recapitulation results of a total score of 1281 from the 6 variables, so that a percentage value of 68.15% was obtained by rounding up to 68% so that it is included in the Implemented category. Based on the results of this analysis, it can be concluded that the implementation of Tabalong Regent Regulation Number 60 of 2019 concerning fees for acquiring land and building rights (BPHTB) at the Regional Revenue Agency of Tabalong Regency is included in the Implemented category Keywords: Implementation, BPHTB, Regional Revenue Agency